The handbook of political economy of communications - Wasko, Janet; Murdock, Graham; Sousa, Helena (Chichester, West Sussex Wiley-Blackwell, 2011)
"Over the last decade, political economy has grown rapidly as a specialist area of research and teaching within communications and media studies and is now established as a core element in university programmes around the world. The Handbook of Political Economy of Communications offers students and scholars a comprehensive, authoritative, up-to-date and accessible overview of key areas and debates. Combines overviews of core ideas with new case study materials and the best of contemporary theorization and research written many of the best known authors in the field. Includes an international line-up of contributors, drawn from the key markets of North and Latin America, Europe, Australasia, and the Far East"-- Provided by publisher.
Introduction: The Political Economy of Communications: Core Concerns and Issues / Janet Wasko, Graham Murdock, and Helena Sousa -- Legacies and Debates. Political Economies as Moral Economies: Commodities, Gifts, and Public Goods / Graham Murdock -- The Political Economy of Communication Revisited / Nicholas Garnham -- Markets in Theory and Markets in Television / Eileen R. Meehan and Paul J. Torre -- Theorizing the Cultural Industries: Persistent Specificities and Reconsiderations / Bernard Miège ; translation by Chloé Salles -- Communication Economy Paths: A Latin American Approach / Martín Becerra and Guillermo Mastrini -- Modalities of Power: Ownership, Advertising, Government. The Media Amid Enterprises, the Public, and the State: New Challenges for Research / Giuseppe Richeri -- Media Ownership, Concentration, and Control: The Evolution of Debate / John D. H. Downing -- Maximizing Value: Economic and Cultural Synergies / Nathan Vaughan -- Economy, Ideology, and Advertising / Roque Faraone -- Branding and Culture / John Sinclair -- Liberal Fictions: The Public-Private Dichotomy in Media Policy / Andrew Calabrese and Colleen Mihal -- The Militarization of US Communications / Dan Schiller -- Journalism Regulation: State Power and Professional Autonomy / Helena Sousa and Joaquim Fidalgo -- Conditions of Creativity: Industries, Production, Labor. The Death of Hollywood: Exaggeration or Reality? / Janet Wasko -- The Political Economy of the Recorded Music Industry: Redefinitions and New Trajectories in the Digital Age / André Sirois and Janet Wasko -- The Political Economy of Labor / Vincent Mosco -- Toward a Political Economy of Labor in the Media Industries / David Hesmondhalgh and Sarah Baker -- Dynamics of Consumption: Choice, Mobilization, Control . From the "Work of Consumption" to the "Work of Prosumers": New Scenarios, Problems, and Risks / Giovanni Cesareo -- The Political Economy of Audiences / Daniel Biltereyst and Philippe Meers -- The Political Economy of Personal Information / Oscar H. Gandy, Jr. -- The Political Economy of Political Ignorance / Sophia Kaitatzi-Whitlock -- Emerging Issues and Directions. Media and Communication Studies Going Global / Jan Ekecrantz -- New International Debates on Culture, Information, and Communication / Armand Mattelart ; translation by Liz Libbrecht -- Global Capitalism, Temporality, and the Political Economy of Communication / Wayne Hope -- Global Media Capital and Local Media Policy / Michael Curtin -- The Challenge of China: Contribution to a Transcultural Political Economy of Communication for the Twenty-First Century / Yuezhi Zhao.
Includes bibliographical references and indexes.
Electronic reproduction.
Keywords: Communication -- Economic aspects; Communication -- Political aspects; Mass media -- Economic aspects; Mass media -- Political aspects; Electronic books